Pengaruh Senam Kegel Dengan Penyembuhan Luka Perineum Pada Ibu Primipara - Astuti, Endang Dwi; Susilawati, Susilawati; Evrianasari, Nita (ANJANI Journal (Medical Science & Healthcare Studies), 2024)
Background: The wound healing in this perineal tear will vary, some are healed normally (6-7 days) and some have experienced healing in their healing. The inhibitors of wound healing according to Maryunani (2014) are as follows: malnutrition, smoking, lack of sleep, stress, medical conditions and therapy, suboptimal smears, optimal environment for wound healing, lack of mobilization and infection. Kegel exercises are exercises to strengthen the pelvic muscles. Poupuse: The research objective has been the influence of Kegel exercises by healing perineal wounds in primiparous mothers in the Wates Health Center, Central Lampung Regency, 2020.Methods: This type of quantitative research, the research design used a Quasi Experimental non-equivalent control group design. The object of research is the effect of Kegel exercises with perineal wound healing. The subjects in this study were all primiparous women giving birth in the Wates Health Center, Central Lampung Regency. The sample in this study in the experimental group may be 20 and the control group assesses 20 respondents. The research site was conducted in the Wates Health Center, Central Lampung Regency in 2020, this research was conducted in February - July 2020.Result:The average wound healing rate in the experimental group before Kegel exercises was 10.65 and after Kegel exercises 4.40. The average wound healing rate in the control group at the first measurement was 10.45 and the second measurement was 5.30. Conclusion: There is an effect of Kegel exercises with perineal wound healing in primiparous mothers in the working area of the Wates Health Center in Central Lampung Regency in 2020, (p-value 0,000 <0.05 and t-test 4.541), there is a difference in wound healing in post partum mothers where mothers who do Kegel exercises heal faster when compared to mothers who did not do Kegel exercises with 1,100 points. Suggestion: This means that it can be put aside that Kegel exercises can accelerate the healing of perineal wounds. It is hoped that health workers will provide health education for post-partum mothers to do Kegel exercises. Keywords: Kegel Exercises, Postpartum ABSTRAKLatar belakang: Penyembuhan luka pada robekan perineum sembuh secara bervariasi, ada yang sembuh normal (6-7 hari) dan ada yang mengalami keterlambatan, dimana dari keter,lambatan ini dapat menyebabkan komplikasi salah satunya adalah perdarahan. Berdasarkan data kasus perdarahan terjadi sebanyak 2,4%, salah satu cara untuk mempercepat penyembuhan luka adalah melakukan senam kegel, dimana fungsi dari senam kegel dapat memaksimalkan aliran darah ke perineum sehingga luka cepat sembuh.Tujuan: di ketahui pengaruh senam kegel dengan penyembuhan luka perineum pada ibu primipara di Wilayah Kerja Puskesmas Wates Kabupaten Lampung Tengah Tahun 2020.Metode: Jenis penelitian kuantitatif, desain Quasi Eksperimental rancangan non equivalent control group Design. Objek penelitian adalah pengaruh senam kegel dengan penyembuhan luka perineum. Subyek seluruh ibu bersalin primipara di Wilayah Kerja Puskesmas Wates Kabupaten Lampung Tengah. Sampel pada kelompok eksprimen berjumlah 20 dan kelompok kontrol berjumlah 20 responden, tekhnik sampling secara purposive sampling. Tempat penelitian telah dilakukan di Wilayah Kerja Puskesmas Wates Kabupaten Lampung Tengah, penelitian ini telah dilakukan pada tanggal 6 Februari – 22 Agustus 2020. pengumpulan data menggunakan kuesioner, analisis data secara univariat dan bivariat (uji t).Hasil: Didapatkan rata-rata penyembuhan luka pada kelompok eksperimen sebelum senam kegel adalah 10,65 dan setelah senam kegel 4.40. Rata-rata penyembuhan luka pada kelompok kontrol pada pengukuran pertama adalah 10.45 dan pengukuran kedua 5.30.Kesimpulan: Ada  pengaruh senam kegel dengan penyembuhan luka perineum pada ibu primipara  di wilayah kerja Puskesmas Wates Kabupaten Lampung Tengah Tahun 2020, (p-value 0,000 < 0,05 dan t-test 4,541), terdapat selisih penyembuhan luka pada kelompok intervensi dengan selisih 1.100 point.Saran: Diharapkan kepada tenaga kesehatan untuk memberikan pendidikan kesehatan sebelum ibu pulang dengan mengajarkan senam kegel dan memberikan booklet pada ibu nifas yang berisi gerakan senam kegel dan perawatan masa nifas dan menyusui. Kata Kunci: Senam Kegel, Nifas